Tax Policy and the Happiness Index - Wojciechowska-Toruńska, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article addresses the relationship between taxation and satisfaction with life. What is known as a happiness index was constructed to perform an approximate analysis of the level of life satisfaction in countries with different tax policies. The hypothesis, which states, ‘Countries with a high happiness index need not have high average tax rates but should be identifiable by their progressive income tax, increased diversification of VAT rates and stable level of public expenditure as a proportion of GDP’ was verified positively. The search for the optimal tax policy should take into account not only economic growth but also the growth rate of social satisfaction and the level of social welfare.